Early maternal separation: Neurobehavioral consequences in mother rats - Aguggia, Julieta Paola (2013)
Repeated separation of dams from their pups during the postpartum period may evoke emotional stress in the dam. In the present study we investigated whether prolonged maternal separation is stressful for rat dams by studying different behavioral and central responses known to be affected by stress. After delivery, female Wistar rats were subjected to either animal facility rearing (AFR) conditions or daily 4.5 h of mother–litter separation from postpartum day (PPD) 1–21. Maternal care (pup retrieval) was evaluated at PPD 3. After weaning on PPD 21, anxiety (elevated plus maze) and depression-like behaviors (forced swimming test) were assessed in the dams. Memory abilities (one-trial step down inhibitory avoidance) were tested either 1 h (short-term memory) or 24 h (long-term memory) after training session. Finally, c-Fos expression was examined in the central nucleus of the amygdala. The results revealed that pup retrieval efficiency at PPD 3 was significantly impaired by maternal separation. AFR dams retrieved their pups sooner and engaged in more pup-directed activities (nest building and carrying pups). Separation from pups increased the number of entries in open arms of the plus maze and decreased latency times in the inhibitory avoidance test for both short and long-term memory in the dams. There were no differences in depression-related behavior as assessed using the forced swimming test. Furthermore, maternal separation yielded high c-Fos expression in the central nucleus of the amygdala. Together, these data indicate that repeated maternal separation in the early postpartum period reduces maternal care and impairs the retention memory, providing further evidence for the detrimental neurobehavioral effects of maternal separation in dams.